Influência de tratamentos de superfície e cimentos resinosos no comportamento mecânico e adesivo de cerâmicas vítreas - Dapieve, Kiara Serafini (2023)
This thesis is composed of five studies. Study 1 evaluated the influence of ceramic bonding surface treatments (application of silane-based coupling agent only – CA, hydrofluoric acid – HF or HF+CA) and storage regimes (with or without aging) on the fatigue behavior of simplified lithium disilicate (LD) restorations. It was observed that aging negatively influenced the performance of all groups. The micromechanical interlocking resulting from the acid etching prevailed in the fatigue behavior; thus, the CA was dispensable for the evaluated outcome. Study 2 evaluated the influence of ceramic bonding surface treatments (HF or self-etching ceramic primer – E&P) and storage regimes (with or without aging) on the bond strength of a resin cement with two viscosities (high or low) to LD ceramic through a microshear test. Furthermore, it investigated the dynamic viscosity of the components of the luting system. Differences in inorganic filler content affected the viscosity of resin cements, which in turn influenced the bond strength to a LD ceramic, according to each surface treatment and storage regime. Study 3 evaluated the influence of the resin cement viscosity (high or low) and the loading mode (static or cyclic fatigue) on the shear bond strength of the resin cement to LD and dentin substrates. Shear under cyclic fatigue presented deleterious effects on the adhesive behavior and survival probabilities of LD bonded sets, regardless of resin cement viscosity. In contrast, resin cement viscosity affected bond strength and survival rates of dentin substrate subjected to cyclic loading mode, in which a low viscosity resulted in better performance. Study 4 evaluated the effect of resin cement viscosity (high or low) and ceramic bonding surface treatments (HF+CA or E&P) of machined LD crowns on mechanical fatigue behavior. HF+CA/high viscosity and E&P/low viscosity showed the best fatigue performance. The behavior of bonded crowns was dependent on the topographic alterations of the ceramic surface and on the luting agent’s ability to fill in the irregularities. Study 5 evaluated the effect of ceramic bonding surface treatments (HF+CA or E&P), resin cement viscosity (high or low), and storage regimes (with or without aging) on the fatigue performance of simplified LD and feldspathic ceramic (FEL) restorations. Aging can negatively influence the mechanical behavior of simplified glass restorations. Furthermore, the "ceramic microstructure relationships - ceramic surface conditioning - resin cement viscosity" modulated the fatigue performance of LD and FEL simplified restorations.